Primer Design For Identification Of Beta-Carotene Encoding Genes In Cassava - mutia anika; Dwi Hilda Putri; Wahyuni Wahyuni (Universitas Negeri Padang, 2019)
Primers are oligonucleotides which have an important role in the PCR process. To get the primer can be done by doing a primary design. Beta-carotene encoding genes are genes that play a role in the formation of beta-carotene in carotenoid biosynthetic pathways in several plants including cassava. This study aims to obtain primers who can identify beta-carotene encoding genes in cassava plants. Primers are designed using primary 3 plus software online. The results obtained were five specific primers, namely PSY, CRTISO, LCY α, LCY β, and BCH primers which could identify beta-carotene coding genes such as PSY, CRTISO, LCY α, LCY β, and BCH on cassava. Primers designed according to the criteria for primary length, GC content and temperature melting for beta-carotene encoding genes in cassava.